Turtle's race with Beaver : a traditional Seneca story - Bruchac, Joseph, 1942- (Dial Books for Young Readers, 2003)
When Beaver challenges Turtle to a swimming race for ownership of the pond, Turtle outsmarts Beaver, and Beaver learns to share.